A checklist of parasites of non‐native populations of the fish rotan Perccottus glenii (Odontobutidae): Communication II. (29th July 2020) - Sokolov, Sergey G.; Reshetnikov, Andrey N.
Abstract: The fish rotan, Perccottus glenii Dybowski, 1877 (Odontobutidae) is one of the most successful fish invaders during 20th and beginning of 21st century in European and Asian fresh waters. The diversity of its parasites within its invaded range was first reviewed by Sokolov, Reshetnikov, et al. (2014). The current paper analyzes new data from 2013 to 2019 on protistan and metazoan parasites of the non‐native populations of this fish. We used information from peer‐reviewed journals, difficult to access grey literature and our own recently obtained original data. 45 literature sources were included in the analysis. The newly‐available data originate from 95 water bodies of 13 river basins, isolated lakes in West Siberia, and Gulf of Finland, spanning a total of eight countries. A total of 132 recently detected parasite species/taxa are listed in this paper. Each species is presented with its location in/on the host, geographical localities, countries, and according literature sources. When available, number of examined fish as well as prevalence and range of intensity of infection are cited from the original source. This review enlarges contemporary knowledge on parasites of non‐native populations of the studied fish species up to 167 species/taxa. We highlight perspectives for further parasitological investigations of this invasive fish.